CFD Analysis to Study the Effect of Geometry in Flow Behavior of Wing Structure with Additional Riblets: Riblets induced Flow using CFD over wing structure - Khan, Muhammad Zia Ullah; Bhutta, Rumeel A.; Asif, Tahir; Farooq, Muhammad; Qamar, Adnan (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Drag reduction have always been the most important area of interest for a decade with many advancement in it, there has been continuous research on the flow behavior of wing with different geometric combination. Previous studies suggest that Riblets are 7% effective given that they are made with correct sizing. According to test conducted shows the near same result of drag reduction up to 5%. In the present research CFD techniques were used to analyze the flow pattern, where geometry was changed in addition to Riblets named as add-ins. Pressure effect and corresponding velocity dynamics were studied. Each reformed airfoil was analyzed using CFD techniques. A structured grid mesh was used. Governing equation were identified to model exact behavior and numerical computation was performed using FEA software. Simple algorithm and second order upwind scheme for pressure discretization, second order upwind scheme for momentum and energy was used. Changing geometric shape shifts pressure regions and more control is obtained on lift. Value extraction zone selected is outer cross-sectional area in close approximation to wing profile using commercially available computational package. ∆P at point 0.05 for design 1,2 and 3 at 0○ is 5400 Pa, 7000 Pa and 100 Pa, at 15○ on far location is 26000 Pa, 4000 Pa and 8000 Pa where on close location is 35000 Pa, 18000 Pa and 5000 Pa which shows good feasibility for first two designs. Design 1 and 4 ∆P at 0.05 is 500 Pa and 4000 Pa. Singular geometric alteration yields better result than plural, any modification to rear section does not affect the flow separation. By doing these amendments on desired points can increasing fuel economy rate for jets and commercial air planes.